Analysis of Internet Network Technology Online Training for Indonesian Navy Information Technology Employees Using Hierarchical Clustering - Suhirwan Suhirwan; Bambang Suharjo (Jurnal Studi Guru dan Pembelajaran, 2021)
During the covid-19 pandemic, all institutions had a high dependency on information technology. Network strength is very important. Thus, an internet network technology course was conducted for information technology personnel of the Indonesian Navy. The training is conducted online. Studied learning success is associated with the initial data held, namely rank, gender, work experience in the field, previous education and learning activities, and age of participants. The data was clustered with the final test results to determine the clustering of training results and these factors. Based on the clustering it can be stated a good grouping of learning success in this pandemic period. From the 75 personnel data, we could made 5 clusters. Recommendation for internet network tools online training, especially in internet network technology, is that the participants of the course should have experience in internet and network, young and have good education level at least high school.